FORMULASI SEDIAAN MASKER Gel Peel Off EKSTRAK ETANOL DAUN JAMBU BIJI (Psidium Guajava L.) SEBAGAI PEMBERSIH WAJAH - Palas Tarigan (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2022)
Guava plants contain psiditanin “eugenol” essential oil, tannis, flavonoids, saponins, alkaloids. Compounds that have very good strength come from the class of flavanoids, vitamin C which can be usedas a facial cleanser. This study aims to determine the preparation of peel gel mask of guava leaf extract is effective as a facial cleanser and to find out the peel off gel mask of guava leaf extract can irritate the skin of volunteers. The made with 4 formulation with concentrations of 0%, 10%, 15%, 20%. The testing of the peel off gel mask formulation ethanol extract on cleanliness was carried out with the analysis of the ms. Excel bar diagram. The results showed that (psidium guajava L) contain flavonoid, alkaloids, tannins and saponins. The results of the characteristics of the simplicia powder were 5,42% water content 9,56% total ash content 0,34% acid insoluble ash, ethanol soluble extract 64,295. The results of the peel off gel mask formulation test with a cleanliness test on the panelists facial skin concentration of 15% included in the category can clean the panelist’s facial skin.Guava leaf ethanol extract has a facial cleansing activitywith a score of 3